Technology platforms in Russia: a catalyst for connecting government, science, and business? - Irina G. Deézina (Triple Helix, 2014)
The article analyzes a new instrument of Russian innovation policy - technology platforms. The reasons for their establishment are outlined based on the analysis of the innovation system in Russia. Comparisons with the European Union technology platforms, which served as blueprints for developing similar structures in Russia, are provided. Russian platforms are found to suffer from the government micromanagement. More detailed analysis is provided through three case studies of selected technology platforms specializing in different representative economic areas. The results of these studies demonstrate that Russian technology platforms are still far from being effective communication instruments. The platforms received inadequate federal support at the initial stages of their development, which eventually affected their performance. Nevertheless, the first steps have been undertaken to create expert communities in important economic areas. The article suggests directions for further development of technology platforms, such as expanding a palette of stakeholders and conducting two-way monitoring - both of platforms' performance and government measures aimed at their development.
Keywords: O31; O32; O38; 330; Innovation policy; European Union; Instruments; Research and development; Russia; Technology platforms